Analysis of the Implementation of Strengthening Character Education Through Pesantren Ramadan - Ahmad Muflih; Achmad Daengs GS; Dawam Multazamy Rohmatulloh; Padjrin Padjrin (AL-ISHLAH: Jurnal Pendidikan, 2022)
Schools play an important role in fostering students' character with various programs in and outside the classroom to fortify students from the negative effects of globalization. This study aims to analyze the implementation of strengthening character education through the Pesantren Ramadan program to develop the religious character of students. The research method used is qualitative with a descriptive approach. Principals, teachers, and students became informants in this study. The data were collected through interviews, observation, and documentation, then the data were analyzed using the triangulation method. This study shows that this school implements the strengthening of school culture-based character education, one of which is the Pesantren Ramadan. This program aims to develop religious character as the main character and other characters such as independence, care for others, and integrity. There are several activities in the Pesantren Ramadan: Azan Competition, Religious Lecture Contest, Calligraphy Competition, Short Letter Memorizing Competition, Tartil Competition, Islamic Poster Contest, Zuhur Prayer, Al-Qur'an Tadarus, Collection of Zakat Fitrah, and Commemoration of Nuzul Al-Qur' an. Thus, the Islamic Boarding School of Ramadan effectively increases students' religious character.